2020
DOI: 10.17811/rifie.49.4.2020.373-384
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia de los distintos tipos de violencia escolar en Educación Primaria y Secundaria

Abstract: El objetivo del estudio era cuantificar los diferentes tipos de violencia escolar que se llevan a cabo en centros de primaria y secundaria, así como analizar si las variables socio-escolares determinan y predicen su desarrollo en estudiantes. Se llevó a cabo una investigación no experimental, descriptiva, inferencial y de regresión. La muestra, intencional y estratificada, fue de 1139 participantes [423 alumnos de primaria (M = 10.56; DT = .67) y 716 alumnos de secundaria (M = 14.09; DT = 1.22)], a los cuales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
2
11
0
5
Order By: Relevance
“…Likewise, men have higher aggressive levels than women in both their manifest and relational expressions. Similar results are consistent with most research studies on sex differences related to aggressive behaviour [ 21 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. In contrast, these findings are opposed to those reflected in the study by Blasco and Orgilés [ 41 ], who found that women were more inclined to physical aggression than men in a population of football players between 7 and 17 years old.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, men have higher aggressive levels than women in both their manifest and relational expressions. Similar results are consistent with most research studies on sex differences related to aggressive behaviour [ 21 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. In contrast, these findings are opposed to those reflected in the study by Blasco and Orgilés [ 41 ], who found that women were more inclined to physical aggression than men in a population of football players between 7 and 17 years old.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have already pointed out the importance of monitoring spaces that are not controlled by adults since these are places where more violent behavior occurs among peers (Landazabal & Ramirez, 2009). These results are also reflected by studies conducted in later secondary school years (Domínguez Rodríguez et al, 2020), underscoring the need for teachers to be able to identify early manifestations of violence to address them (Santana, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…These results are also reflected by studies conducted in later secondary school years (Domínguez Rodríguez et al, 2020), underscoring the need for teachers to be able to identify early manifestations of violence to address them (Santana, 2018).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations